The impact of a proposed training curriculum to develop explosive power and shooting skill in basketball (Journal of the College of Basic Education, 2022)
The lesson of the game of basketball is one of the important lessons in the faculties of physical education, as students study it for a period of three years, and its theoretical and practical laws and its applied skills are among the most difficult topics for the various games, as the physical strength with which basketball skills are performed is characterized by high physical strength that requires players, coaches and referees to prepare The type of integrated preparation, skillfully, planning, educationally and theoretically. Absorbing its laws requires high-level thinking that contributes to the production of creative intellectual forces and advanced physical forces that work to succeed and improve the level of basketball players in terms of performance and skill.